A NARRATIVE REVIEW ON SYNERGISTIC ACTION OF VITAMIN D, GLUTAMINE AND ONCOTHREAD IMMUNOMODULATORS IN INTERFERON SIGNALLING AND COVID 19 - Dr Sunayna Juneja; Dr Yeshwant Lamture; Dr Shubhi Gupta; Dr Chetan Agrawal (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
The reason behind the Novel Coronavirus disorder 2019 (COVID-19) is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that was found in Wuhan, China, in December 2019. The investigation into the best pharmacotherapy continues as it makes rapid progress in covering a wide range of nations. It is known that coronaviruses, such as SARS-CoV-19, can mask Associate in Nursing stand back from the host organism’s antiviral responses. Antiviral (IFN), a family of cytokines that plays a critical role in antiviral resistance concerning the body’s defense mechanism and has been used therapeutically for persistent viral infections, mediates these responses. OncoTherad, a reliable and effective adoptive immunotherapy for the treatment of non-muscle invasive bladder cancer (N.M.I.B.C.), will increase IFN signaling and be shown to be a promising recovery strategy for COVID-19 in a trial that reflected the rapid recovery of a 78-year-old NMIBC patient with comorbidities. This takes into account targets to determine the viable synergistic motion of OncoTherad with vitamins like zinc and glutamine, vitamin d. These microelements play a crucial role in strengthening the body’s defenses and fighting off pathogens through various mechanisms. For example, vitamin d is anti-inflammatory and also helps in the prevention of tissue injury by inhibiting cytokines. Zinc is essential for the development and proper functioning of immune cells, as well as for preventing viral replication. Glutamine acts as a fuel reservoir for immune cells and also possesses antioxidant properties. Therefore, providing adequate nutritional support from micronutrients can have a positive impact on the outcome of COVID19. have been validated to facilitate immune responses mediated with the aid of using I.F.N. signaling, in addition to the ability of this mixture in regulating immune characteristic withinside the remedy of COVID-19. This article briefly focuses on how micronutrients like zinc, vitamin D, and glutamine interact with the synergistic presence of interferons and oncotherad in the therapy regimen for COVID-19.